Tourists’ intention to visit Bangka Island: How far does publicity affect destination awareness, preference and image? - Suhud, Usep; Allan, Mamoon; Hoo, Wong Chee; Liau, Chee How; Aryansyah, Ary Fakturrachman (Edelweiss Applied Science and Technology, 2024)
This research aims to analyse factors that affect the tourists' intention by visiting Bangka Island, Indonesia, studying predictors that include destination publicity, awareness, image, and preference; this comprehensive approach is very rarely applied to island tourism. A total of 230 tourists were approached for participation in this study with an appropriate sampling method. The data were analysed using exploratory factor analysis, confirmatory factor analysis, and structural equation modelling. The results revealed that destination publicity has a significant influence on destination awareness, destination image, and destination preference. However, the study found that intention to visit was significantly influenced by knowledge about the destination and perceptions of the place. Choice of destination, however, had a minimum effect on desire to visit. These findings, in addition to enhancing our understanding of consumer behaviour and destination marketing in island tourism, reiterate the importance of good publicity within a country, showing just how awareness and image impact tourists' disposition toward visiting a destination and therefore offering valuable lessons for all stakeholders in tourism. This study indicates that effective destination publicity and improved destination awareness and image can contribute to the creation of economic growth and new jobs in island destinations like Bangka Island, while at the same time enhancing forms of responsible tourism that promote sustainable use of resources and reduce negative impacts on the environment. Thus, it would have very relevant repercussions on SDG 8: Decent Work and Economic Growth, and SDG 12: Responsible Consumption and Production.